Immune Stimulation Using a Gut Microbe-Based Immunotherapy Reduces Disease Pathology and Improves Barrier Function in Ulcerative Colitis - Sham, Ho Pan; Bazett, Mark; Bosiljcic, Momir; Yang, Hyungjun; Luk, Beryl; Law, Hong T.; Morampudi, Vijay; Yu, Hong B.; Pankovich, Jim; Sutcliffe, Simon; Bressler, Brian; Marshall, John K.; et al. (Frontiers in Immunology, 2018)
Background: Current ulcerative colitis (UC) treatments are focused on symptom management primarily via immune suppression. Despite the current arsenal of immunosuppressant treatments, the majority of patients with UC still experience disease progression. Importantly, aggressive long-term inhibition of immune function comes with consequent risk, such as serious infections and malignancy. There is thus a recognized need for new, safe and effective treatment strategies for people living with UC that work upstream of managing the symptoms of the disease. The objective of this study was to evaluate a microbial-based treatment, QBECO, that functions to productively activate rather than suppress mucosal immune function as a novel approach to treat UC. Methods: Two established models of experimental colitis, namely chemically-induced DSS colitis and the spontaneous colitis that develops in Muc2 deficient mice, were used to assess whether QBECO treatment could ameliorate gastrointestinal disease. A small exploratory 16-week QBECO open-label trial was subsequently conducted to test the safety and tolerability of this approach and also to determine whether similar improvements in clinical disease and histopathology could be demonstrated in patients with moderate-to-severe UC. Results: QBECO treatment successfully reduced inflammation and promoted mucosal and histological healing in both experimental models and in UC patients. The preclinical models of colitis showed that QBECO ameliorated mucosal pathology, in part by reducing inflammatory cell infiltration, primarily that induced by neutrophils and inflammatory T cells. The most rapid and noticeable change observed in QBECO treated UC patients was a marked reduction in rectal bleeding. Conclusion: Collectively, this work demonstrates for the first time that strategically activating immune function rather than suppressing it, not only does not worsen colitis induced-damage, but may lead to an objective reduction in UC disease pathology.